Laminar Flame Characteristics of 2,5-Dimethylfuran (DMF) Biofuel: A Comparative Review with Ethanol and Gasoline - Long Vuong Hoang; Danh Chan Nguyen; Thanh Hai Truong; Huu Cuong Le; Minh Nhat Nguyen (International Journal of Renewable Energy Development, 2022)
Since the early years of the 21st century, the whole world has faced two very urgent problems: the depletion of fossil energy sources and climate change due to environmental pollution. Among the solutions sought, 2,5-Dimethylfuran (DMF) emerged as a promising solution. DMF is a 2nd generation biofuel capable of mass production from biomass. There have been many studies confirming that DMF is a potential alternative fuel for traditional fuels (gasoline and diesel) in internal combustion engines, contributing to solving the problem of energy security and environmental pollution. However, in order to apply DMF in practice, more comprehensive studies are needed. Not out of the above trend, this paper analyzes and discusses in detail the characteristics of DMF's combustible laminar flame and its instability under different initial conditions. The evaluation results show that the flame characteristics of DMF are similar to those of gasoline, although the burning rate of DMF is much higher than that of gasoline. This shows that DMF can become a potential alternative fuel in internal combustion engines.